2008
DOI: 10.1002/ajim.20647
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation incidents and respiratory health: results from the European Community respiratory health survey

Abstract: Background-Inhalation incidents are an important cause of acute respiratory symptoms, but little is known about how these incidents affect chronic respiratory health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the longitudinal European Community Respiratory Health Survey, it was found that retrospectively reported acute inhalations were associated with new-onset asthma (40). A more detailed analysis in this population showed that reporting bias could not be discarded; individuals with any respiratory problems at baseline were more likely to report inhalation incidents 9 years later (41). Cross-sectional studies also found that asthmatics more often had a history of single high exposure to irritant cleaning products than healthy controls (42)(43)(44).…”
Section: Epidemiological Evidence For Irritant-induced Asthmamentioning
confidence: 86%
“…In the longitudinal European Community Respiratory Health Survey, it was found that retrospectively reported acute inhalations were associated with new-onset asthma (40). A more detailed analysis in this population showed that reporting bias could not be discarded; individuals with any respiratory problems at baseline were more likely to report inhalation incidents 9 years later (41). Cross-sectional studies also found that asthmatics more often had a history of single high exposure to irritant cleaning products than healthy controls (42)(43)(44).…”
Section: Epidemiological Evidence For Irritant-induced Asthmamentioning
confidence: 86%
“…Acute inhalation accidents can cause short-tem and longer-term lung damage and are normally associated with a single high-level inhaled exposure. A wide variety of agents are implicated 4. Irritant gases, such as chlorine,5 are well understood to produce airway injury, but certain low molecular weight chemicals (such as isocyanates6), other irritant agents (such as ozone7) and complex mixtures8 are also implicated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their importance, real-world data about their causes, commonly represented industries and associated occupations and incidence remain relatively poorly understood. Previous epidemiological work suggests that episodes of exposures to high levels of pollutants are common 4. Recent SWORD based analysis has also identified a link between exposures to cleaning agents and inhalation accidents 9…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure-induced lung diseases are the primary cause of occupation-associated illness in the United States 28 . The rates of acute inhalation incidents are not well known but have been largely attributable to lack of adequate respiratory or ventilation equipment, equipment failure, leaks/spills, accidents, fires, disasters, among others with treatment consisting of supportive care approaches including oxygen, bronchodilators, and sometimes corticosteroids 29 , 30 . Using high concentration acute LPS inhalation animal modeling, these current time continuum studies demonstrated a rapid rise/recovery in weight loss, proinflammatory mediators, neutrophils, and lymphocytes, but also a prolonged persistence of activated macrophage and recruited/transitioning monocyte-macrophage subpopulations.…”
Section: Discussionmentioning
confidence: 99%